The Anti-Obesity Effects of Morus alba: A Literature Review - Redner, Aneta; Sikora, Gabriela; Woźniak, Martyna; Sajda, Małgorzata; Kutnik, Karolina; Koguc, Karolina; Kusibab, Karolina; Czechowski, Michał; Skórska, Gabriela; Słomianny, Marcela; Kolada, Karolina (Quality in Sport, 2025)
Purpose: This literature review explores the anti-obesity potential of Morus alba (white mulberry) and its role in the prevention and management of obesity. It highlights the mechanisms by which Morus alba may influence metabolic pathways related to fat accumulation, lipid metabolism, inflammation, and gut microbiota modulation. Methodology: A narrative review of 20 selected peer-reviewed studies was conducted, focusing on experimental and preclinical evidence of Morus alba’s metabolic effects. Key areas of interest included lipid regulation, adipogenesis, antioxidant activity, and interactions with the gut microbiota. Findings: The studies reviewed suggest that Morus alba exhibits significant anti-obesogenic effects through various mechanisms, including inhibition of lipid accumulation, regulation of adipogenic gene expression, enhancement of fatty acid β-oxidation, activation of AMPK signaling, and improvement in glucose metabolism. Some studies also report its potential to restore gut microbial balance in obesity models. Conclusions: Morus alba represents a promising candidate for complementary obesity management strategies due to its multifactorial action on adiposity, metabolism, and inflammation. However, more clinical trials are needed to determine effective dosages and long-term safety in humans.